Characterization of musculoskeletal injuries in gymnastics participants from 2013 to 2020 - Albright, J. A.; Meghani, O.; Lemme, N. J.; Owens, B. D.; Tabaddor, R. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Many studies have analyzed gymnastics-related injuries in collegiate and elite athletes, but there is minimal literature analyzing the epidemiological characteristics of injuries in the greater gymnastics community.